Translation and cultural validation of the Revised Illness Perception Questionnaire for Healthcare Professionals for Brazilian Portuguese - De Nigris Vasconcellos, Fernando; Lima, Felipe Gregório; Oliveira, Enedina Maria Lobato de (Arquivos de Neuro-Psiquiatria, 2021)
Background: Multiple sclerosis progression and disability can be rated differently by healthcare professionals. Therefore, how physicians perceive the disease can impact treatment decisions. There are no previous studies on this matter. Objective: To translate and transculturally validate the Revised Illness Perception Questionnaire for Healthcare Professionals (IPQ-R HP), for use in Brazilian Portuguese. Methods: The process used to validate the IPQ-R HP was based on the steps presented in the guide proposed by Dorcas Beaton. The final version of the IPQ-R HP had 38 questions, divided into seven different dimensions to assess the patient's disease. Also, two clinical cases that were representative of real-life patients with multiple sclerosis (MS) were assembled to consider the two main profiles of the disease. We applied the questionnaire to neurologists at the Federal University of São Paulo (UNIFESP) to assess their perception of MS. These doctors also answered a brief survey to establish the profile of the interviewees. For statistical analysis, we used Bayesian CFA models and kappa statistics. Conclusions: The kappa statistics showed a general agreement of 0.4. For the Bayesian CFAs with seven-factor correlation solution, we had a poor fit for case 1 with a 95% confidence interval ranging from -52.893 to 273.797 and a PPP of 0.107. Regarding case 2, the model did not converge even after 50,000 iterations, which indicated that the specified model (i.e. seven-factor correlation solution) for case 2 was inadmissible. Thus, the IPQ-R HP questionnaire in Brazilian Portuguese has not been validated.
Keywords: Multiple Sclerosis; Surveys and Questionnaires; Disease; Perception; Validation Study